Pengaruh Emotional Branding and Brand ldentity Terhadap Loyalitas Konsumen Coffee Shop di Yogyakarta - Petra Surya Mega Wijaya; Jonathan Herdioko (Jurnal Riset Manajemen dan Bisnis, 2010)
The coffee shop industry in Yogtakarta is growing rapidly. Somelocatiotu arotmd the campuses become the strategic locations for the coffee shops. These shops are altractive alternatives for the people especially the stadents for discttssions or social interactions. They offer variuts serttice alternatives in accordancewith their segments. on cmerage, the industry offersaffardable prices for all Hnds of ctstomers especially students with qcellent senices. The competition among the shops is diverse to attract costumers in forns of the menus, drinb, hotspotfacility, live music, etc.Nearly every night especially on Scurdays or &ring holidays, thecoffee shops become the main destinations of people. The phenomenon is interesting to study especially the attitudes of the castomers of the coffee shops in Yogtalrarta. With the reason, this research attempts to see the influmce ofemotional branding and brand identity on the loyalty of the anstomers of the coffee shops in Yogtakarta.To lotow the inJluence, there were 200 questionnatres distributed to the people who have visited od shopped in the coffee shops in Yogtalarta &tring six montlzs since this research began. The analysis instrwnent to arutwer the lrypothesis is Strtrctural Equation Model (SEM).  The analysis indicates o significant influence on the relational vwiable on the brand as person, the fue serutes uperierce variable toward the brand as prgfluct, the imagery variable toward the brands as pro&tct, thebrand as person, and the Walty, as well as the brond as person variable toward loyalty. In addition, there is a non-signiJicant inJluence, namely the relatiorwl variable toward the brod as product, and loyalty, the five-serce wperience voriable toward the brmtd as person and loyalty, as weli the brondvriable as product toward loyalty.Kelwords: Emotional Branding, Brand ldentity, Loyalty, SEM, Coffee Shop Industry